Packet Caches on Routers: The Implications of Universal Redundant Traffic Elimination - Anand, Ashok; Gupta, Archit; Akella, Aditya; Seshan, Srinivasan; Shenker, Scott (University of Wisconsin-Madison Department of Computer Sciences, 2008)
Many past systems have explored how to eliminate redundant transfers from network links and improve network efficiency. Several of these systems operate at the application layer, while the more recent systems operate on individual packets. A common aspect of these systems is that they apply to localized settings, e.g. at stub network access links. In this paper, we explore the benefits of deploying packet-level redundant content elimination as a universal primitive on all Internet routers. Such a universal deployment would immediately reduce link loads everywhere. However, we argue that far more significant network-wide benefits can be derived by redesigning network routing protocols to leverage the universal deployment. We develop ?redundancy-aware? intra- and inter-domain routing algorithms and show that they enable better traffic engineering, reduce link usage costs, and enhance ISPs? responsiveness to traffic variations. In particular, employing redundancy elimination approaches across redundancy-aware routes can lower intra and inter-domain link loads by 10-50%. We also address key challenges that may hinder implementation of redundancy elimination on fast routers. Our current software router implementation can run at OC48 speeds.